Climate stories: Why do climate scientists and sceptical voices participate in the climate debate?. (October 2017) - Sharman, Amelia; Howarth, Candice
Public perceptions of the climate debate predominantly frame the key actors as climate scientists versus sceptical voices; however, it is unclear why climate scientists and sceptical voices choose to participate in this antagonistic and polarised public battle. A narrative interview approach is used to better understand the underlying rationales behind 22 climate scientists' and sceptical voices' engagement in the climate debate, potential commonalities, as well as each actor's ability to be critically self-reflexive. Several overlapping rationales are identified including a sense of duty to publicly engage, agreement that complete certainty about the complex assemblage of climate change is unattainable and that political factors are central to the climate debate. We argue that a focus on potential overlaps in perceptions and rationales as well as the ability to be critically self-reflexive may encourage constructive discussion among actors previously engaged in purposefully antagonistic exchange on climate change.